The impact of methamphetamine/amphetamine use on receipt and outcomes of medications for opioid use disorder: a systematic review - Frost, Madeline C.; Lampert, Hannah; Tsui, Judith I.; Iles-Shih, Matthew D.; Williams, Emily C. (Addiction science & clinical practice, 2021)
Methamphetamine/amphetamine use has sharply increased among people with opioid use disorder (OUD). It is therefore important to understand whether and how use of these substances may impact receipt of, and outcomes associated with, medications for OUD (MOUD). This systematic review identified studies that examined associations between methamphetamine/amphetamine use or use disorder and 3 classes of outcomes: (1) receipt of MOUD, (2) retention in MOUD, and (3) opioid abstinence during MOUD. We searched 3 databases (PubMed/MEDLINE, PsycINFO, CINAHL Complete) from 1/1/2000 to 7/28/2020 using key words and subject headings, and hand-searched reference lists of included articles. English-language studies of people with documented OUD/opioid use that reported a quantitative association between methamphetamine/amphetamine use or use disorder and an outcome of interest were included. Study data were extracted using a standardized template, and risk of bias was assessed for each study. Screening, inclusion, data extraction and bias assessment were conducted independently by 2 authors. Study characteristics and findings were summarized for each class of outcomes. Thirty-nine studies met inclusion criteria. Studies generally found that methamphetamine/amphetamine use or use disorder was negatively associated with receiving methadone and buprenorphine; 2 studies suggested positive associations with receiving naltrexone. Studies generally found negative associations with retention; most studies finding no association had small samples, and these studies tended to examine shorter retention timeframes and describe provision of adjunctive services to address substance use. Studies generally found negative associations with opioid abstinence during treatment among patients receiving methadone or sustained-release naltrexone implants, though observed associations may have been confounded by other polysubstance use. Most studies examining opioid abstinence during other types of MOUD treatment had small samples. Overall, existing research suggests people who use methamphetamine/amphetamines may have lower receipt of MOUD, retention in MOUD, and opioid abstinence during MOUD. Future research should examine how specific policies and treatment models impact MOUD outcomes for these patients, and seek to understand the perspectives of MOUD providers and people who use both opioids and methamphetamine/amphetamines. Efforts to improve MOUD care and overdose prevention strategies are needed for this population.